GE_GERICHTE P/2696/2019 vom 29. Januar 2020 - GE Cour de justice (2020)
PRÉSENTATION DEVANT L'AUTORITÉ;APPRÉHENSION;FLAGRANT DÉLIT;PROPORTIONNALITÉ;RECHERCHE DE L'INDIVIDU | CPP.197; CPP.205; CPP.210; CPP.217